Acoustic-Field Beamforming for Low-Power Portable Ultrasound. (July 2021) - Hu, Chang-Lin; Wu, Guo-Zua; Chang, Chih-Chi; Li, Meng-Lin
Portable ultrasound has been extensively used for diagnostic applications in health monitoring, emergency rooms, and ambulances. However, these handheld ultrasound systems may suffer from heat and battery issues attributed to the large power consumption of the transmitter. Additionally, the largest portion of the direct current (DC) power consumption can be attributed to the amplifier in the digital-to-analog converter (DAC) of the transmitter and to the analog-to-digital converter (ADC) of the receiver. Therefore, the number of transmit/receive channels in a portable ultrasound instrument is one of the crucial design factors regarding heat and battery related issues. To address these problems, we propose an acoustic-field beamforming (AFB) technique for low-power portable ultrasound systems with a single receive and five transmit channels. Finally, the simulation, experimental, and in vivo results verified the feasibility of this approach.